Konsep Ruh dalam Perspektif Psikologi Pendidikan Barat dan Islam - Samad, Sri Astuti A. (LP2M IAIN Samarinda, 2015)
This paper explains the concept of ruh in the context of western and Islamic perspectif using psychology and temathic tafsir as its analysis tool. The term of â€ruhâ€ refers to the description of human both physically and psychologically. It involves 3 dimensions; al-jismiah, al-nafsiyah and al-ruhaniah. al-jismiah deals with the dimension of al-jism (body) and its physical organs. al-nafsiyah consists ofÂ al-aqal, al-nafs and al-qalb. al-ruhaniah consists of al-ruh and fitrah. Western psychology,-pyshoanalysis, behaviorsim, and humanism-, is misuse in interpreting al-ruh. The dimension of al-ruh is the place of the seed of religion. Western psychology views the structure of human psychology reducibility and reductivelly. Islamic psychology, which develops the concept of human structure basedÂ on the understanding of Al-Qur;an, can accomodate that concept as long as it can be places proportionally in the system of the human spirit structure. The dimension of al-ruh can be collaborated and applied furthermore with the methods of former ulama by using more modern approaches, that is, the methods of riyadah, zikir, tazkiyah al-nufus and other methods.